2021
DOI: 10.3390/su13084135
|View full text |Cite
|
Sign up to set email alerts
|

BraveNet Upstander Social Network against Second Order of Sexual Harassment

Abstract: Gender-based violence and domestic violence constitute a huge problem all across countries and continents. The COVID-19 outbreak and the lockdown produced as a consequence of it have contributed to escalating this problem. Many national organisms reported an increase in the data on domestic violence during confinement. Bystander intervention often constitutes one of the most effective mechanisms of attention. The problem is that bystanders do not always dare to intervene. This article aims to provide knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…In all, this policy and social impact is possible also because of the scientific impact of the studies made by the members of MeToo University and their supporters. Several articles have been published in top-ranked scientific journals of different disciplines analyzing: the quantitative and qualitative dimensions of gender violence in Spanish universities (Valls, Puigvert, Melgar & Garcia-Yeste, 2016), the concept and the name of Isolating Gender Violence (Vidu, Puigvert, Flecha & López de Aguileta, 2021), the IGV as the first reason to do not support victims (Melgar, Geis-Carreras, Flecha & Soler, 2021), the consequences of IGV for the health of supporters (Aubert & Flecha, 2021), the typology of the victims of IGV (Flecha, 2021), the pioneer legislation on IGV (Vidu, Tomás & Flecha, 2021), the media that take position in support of harassers (Madrid, Joanpere, De Botton, Campdepadrós, 2020), the media working with the professional criteria of journalism (Pulido, Villarejo, Vidu, Ramis, & Flecha,2021), the first international conference of IGV (Vidu, Valls, Puigvert, Melgar & Joanpere, 2017), how new alternative masculinities respond to the demands of support of victims (Nazareno, Vidu, Merodio & Valls, 2022), and also concrete cases that happened during the hard lockdown imposed in Spain due to COVID-19 (Puigvert, Vidu, Melgar & Salceda, 2021).…”
Section: The Metoo University and The Legislations Against Isolating ...mentioning
confidence: 99%
“…In all, this policy and social impact is possible also because of the scientific impact of the studies made by the members of MeToo University and their supporters. Several articles have been published in top-ranked scientific journals of different disciplines analyzing: the quantitative and qualitative dimensions of gender violence in Spanish universities (Valls, Puigvert, Melgar & Garcia-Yeste, 2016), the concept and the name of Isolating Gender Violence (Vidu, Puigvert, Flecha & López de Aguileta, 2021), the IGV as the first reason to do not support victims (Melgar, Geis-Carreras, Flecha & Soler, 2021), the consequences of IGV for the health of supporters (Aubert & Flecha, 2021), the typology of the victims of IGV (Flecha, 2021), the pioneer legislation on IGV (Vidu, Tomás & Flecha, 2021), the media that take position in support of harassers (Madrid, Joanpere, De Botton, Campdepadrós, 2020), the media working with the professional criteria of journalism (Pulido, Villarejo, Vidu, Ramis, & Flecha,2021), the first international conference of IGV (Vidu, Valls, Puigvert, Melgar & Joanpere, 2017), how new alternative masculinities respond to the demands of support of victims (Nazareno, Vidu, Merodio & Valls, 2022), and also concrete cases that happened during the hard lockdown imposed in Spain due to COVID-19 (Puigvert, Vidu, Melgar & Salceda, 2021).…”
Section: The Metoo University and The Legislations Against Isolating ...mentioning
confidence: 99%
“…Además, la penalización no es solo para quienes se resisten sino también para quienes les apoyan ya que no hay todavía actuaciones destinadas a superar la violencia de género de segundo orden, es decir, la violencia contra quienes apoyan a quienes están sufriendo violencia de género de primer orden. Hay investigaciones ya publicadas que demuestran las represalias para las chicas que se niegan a "morrearse" con un determinado chico y también para quienes las apoyan, represalias que constituyen crueles actuaciones de la violencia machista de primer orden y de la violencia machista de segundo orden (Flecha, 2021;Puigvert et al, 2021). Sin embargo, cada vez hay más escuelas que implementan actuaciones educativas de éxito que promueven una convivencia basada en el rechazo hacia actitudes violentas y el apoyo a las víctimas, sustituyendo a través del diálogo igualitario los actos comunicativos de poder por los dialógicos (Segovia Aguilar, 2017).…”
Section: Consentimientounclassified
“…The environment and our perception of it now play a key role in human behavior and, also, in how people act in their daily lives [ 15 ]. In the same line, it has been shown that the way in which a company deals with equality issues determines not only a good working environment and the well-being of its workers, but also its benefits in the market [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Facing this reality, several mechanisms concerning GBV and survivors’ protection started to be reviewed and reinforced during the lockdown. The Hackathon EUvsVirus constitutes one example in this regard [ 28 ], wherein the EC asked researchers from different countries and disciplines to join forces and build together solutions to support potential victims of GV during the lockdown. In the same line, the “open doors” initiative was built as a mechanism to prevent child abuse during the confinement caused by the pandemic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%